Determinación de la energía de fractura para concreto reforzado con fibras cortas de acero (SFRC) (2013)
The addition of short fibers of steel to concrete is a technique that has been developing for several decades and that gave rise to concrete reinforced with short fibers of SFRC steel, the presence of steel fibers in the concrete matrix affects the properties of the fresh mix, for which specific requirements are required for its preparation (ACI, 2008), the mixtures added with steel fibers bring an improvement in their performance, observed the improvement as reduction of the cracking by shrinkage, increase in the tensile strength and increase in the ductility of the mixture. The increase in the specific energy of fracture GF, in concrete reinforced with fiber, is much more considerable than the increase of the rest of the mechanical properties observed (CHUANBO, 2006), this parameter obtained from the nonlinear fracture mechanics represents adequately the inelastic incursion of the concrete since through the dissipation of energy during the formation, and the growth of the fracturing process, the improvement in concrete performance is quantified adequately.